Breast Cancer Statistics in the European Union: Incidence and Survival across European Countries - Dafni, Urania (Breast Care (Basel), 2019)
The current status and time trends in breast cancer incidence and survival in the 28 European Union countries (EU-28) is presented here. Rates reported are age adjusted and standardized (ASR). A high incidence and high survival rates were observed in the Northern and Western European countries, with the exception of the Baltic countries. The higher incidence is partly attributed to the higher prevalence of lifestyle risk factors, while the higher survival is attributed to better access to beneficial treatments and general health care. Most of the countries in Southern Europe or the former Eastern Bloc have not yet reached the high GDP per capita status (2017 purchasing power parity; PPP) of the earlier established Western democracies. The breast cancer incidence and survival are associated with the PPP level (both higher for the higher PPP category; 2017 PPP above USD 40,000). Overall, a trend toward higher survival rates was observed throughout this first period of the 21st century, with the incidence for most countries either stabilizing at the 2010 levels or decreasing further.